Role of Economic Freedom in Attracting Investments in the Context of Azerbaijan - Suleymanov, Elchin; Alirzayev, Elvin; Talibli, Mammad (International Journal of Economics and Financial Issues, 2019)
Since foreign investments are crucial in developing economy and breaking poverty chain, the majority of developing countries, which suffer from the lack of investment savings in countries, enter the competition in attracting investments. In the competition, they realize that economic freedom has to be improved for investments to come to the economy as well as other freedom level indices. This paper analyzes the key factors needed to better off in order to attract investments, the linkage between foreign capital and the level of freedom of countries investigated in theory and practice, and Azerbaijan’s current economic freedom level and improvements. Sharp decline in oil prices since 2015 that forced government to devaluate the currency twice lead to government reforms in non-oil sector in Azerbaijan. This study also investigates impact of Azerbaijan economic freedom level improved by economic and legislative reforms on economic freedom indices set by World Bank Doing Business and other organizations. Keywords: Economic Freedom, Attract Investments, Azerbaijan Economy, JEL Classifications: R11, E61, K20 DOI: https://doi.org/10.32479/ijefi.5972